Tambakasri BUMDes Branding Assistance in Increasing Organizational Value - Izzalqurny, Tomy Rizky; Muhammad, Muhammad; Utomo, Muhammad Andry Prio; Ferdiansyah, Rifaldy Adinandra (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The purpose of this study is to explore the efforts to develop the economy and improve the quality of life of the community in Tambakasri Village, Tajinan District, Malang Regency, East Java. It focuses on the role of Micro, Small, and Medium Enterprises (MSMEs) in developing the local economy and the need for digital marketing and graphic design skills in promoting MSME products in the digital era. Method: The study employs a service program that includes initial observation, counseling, mentoring, and evaluation. Observations are conducted to understand the situation and needs in Tambakasri Village. Counseling and mentoring involve training in using Canva and social media for digital marketing. An evaluation is carried out to measure the impact of the training program. Practical Applications: The practical application of this study lies in its potential to enhance the capabilities of MSMEs in digital marketing and product design. This is achieved through training in the use of Canva and social media, which are key tools in the digital era. The study shows that these skills can have a positive impact on village economic development and help MSMEs compete in the digital era. Conclusion: The results of this service program show an increase in MSME capabilities in digital marketing and product design. This has a positive impact on the economic development of Tambakasri Village, demonstrating the importance of digital skills in helping MSMEs compete in the digital era. The study concludes that digital marketing and graphic design are key to promoting MSME products and contributing to sustainable economic growth.